Students' motivation in reading test responses washback effect on learning in higher education - Hasanudin, Hasanudin; Akib, Muhaiminah; Said, Erpin; Wael, Ahmad; Hartanti, Rezkiah (KnE Social Sciences, 2023)
This article reported the result of investigation washback on students learning and motivation along Reading subject as a test for EFL learners. Two main aspects were studied: students’ perception of the exam (attitude, content, methodology, course, and preparation) and student perceived to their motivation. A mixed-methods approach utilized to address the issue. Descriptive and frequency scale used to analyze quantitative data obtained from surveying 120 students. For qualitative, the data analysis elicited from observations of two classes and interviews with 12 students as representatives of four levels. The study found that students expressed positive rather than negative washback to both variables (i.e., learning and motivation) toward the exam. Findings indicated that the subject meets their needs and the test appropriate to measure their achievement goals. However, high-stakes testing still has leftover doubt feeling in preparation. Otherwise, the motivation, which covered content, methodology, and attitude, indicated, there is a positive attitude that affects students’ development, and it brings students to get an optimal point on the test. Keywords: Students learning; motivation; students’ perception